Seeing like an international organisation - Broome, Andre; Seabrooke, Leonard 1974- (Routledge, 2014)
This book contributes to the study of International Organizations (IOs) by providing a sharp focus on how IOs' "analytic institutions" interact with states over key policy issues. Analytic institutions include the areas, departments, committees, adjudicatory bodies, and others housed by or linked to IOs that develop the cognitive framework for identifying, understanding, and solving policy problems. Analytic institutions make the state "legible" to IOs and are the key means for how IOs "see" their member states, shaping how international political and economic problems are understood. This book investigates why seeing like an IO matters through cases on leading organizations for global economic governance, including the International Monetary Fund, the World Bank, the Bank for International Settlements, the Organisation for Economic Co-Operation and Development, and the World Trade Organization. The contributors demonstrate the benefits of studying IOs "from the inside-out" to enrich our understanding of why issues in the international political economy are governed the way they are.